Blended-problem based learning with integrated social media-based learning media in improving students' critical thinking skills - Samuel Agus Triyanto; W Wahidin; Nina Hartania; Ai Solihat; S Sutrisno (Biosfer: Jurnal Pendidikan Biologi, 2022)
SMAN 1 Tasikmalaya organizes education and learning that leads to 21st Century skills. One of the 21st Century skills developed is students' critical thinking skills. The critical thinking skills of class XI MIPA 1 student in the 2021/2022 Academic Year, especially in learning biology based on the results of interviews with biology subject teachers, still need to be improved, this is confirmed by the results of the students' critical thinking skills test with an average of 49.85 with the category still underdeveloped. The purpose of the study was to determine the role of Blended-Problem Based Learning with integrated social media-based learning media in improving critical thinking skills of class XI MIPA 1 student. This research was a Classroom Action Research based on Lesson Study. Data on critical thinking skills were obtained using a critical thinking test with essay type questions. Data on students' critical thinking skills test results were analyzed descriptively qualitatively by referring to the Illinois Critical Thinking Essay Test. The results showed that the critical thinking test results for students in cycle I and cycle II had increased by 9.83%, which means that the critical thinking skills of class XI MIPA 1 student in the 2021/2022 Academic Year had developed well in learning biology using Blended-Problem Based Learning with integrated social media-based learning media.